SECONDARY PROCESSES OF PROPANE AND BUTANE MIXTURE AND THEIR THERMODYNAMIC PROBABILITY - Sanjar Saidqulov (Innovate Conferences, 2025)
During the thermal decomposition of a fraction consisting of a mixture of propane and butane at high temperatures in the absence of air, not only primary dehydrogenation and cracking reactions occur, but also various secondary reactions [1-3]. These secondary reactions are mainly associated with the formed unsaturated low-molecular hydrocarbons (ethylene, propylene, etc.), which, due to their high reactivity, undergo various rearrangements and complex transformations in various directions. Dimerisation and trimerisation of olefins. Unsaturated hydrocarbons such as ethylene and propylene can react with each other at high temperatures without the participation of a catalyst, forming large molecular hydrocarbons [4-7].
Keywords: Sanjar Saidqulov